Досвід проектування та будівництва виробництва екологічних меблів на прикладі нового заводу компанії «Вудман» в селі Крехів, Львівської області - Іванов-Костецький, Сергій; Ivanov-Kostetskyi, Serhii (Видавництво Львівської політехніки, 2022)
У публікації висвітлено досвід проєктування підприємства виробництва екологічних меблів, де автор статті виступав співавтором концепції та архітектурноінженерної ідеї комплексу будівель і споруд, був головним архітектором, а також виконавцем частини розділів проєкту будівництва Заводу ВУДМАН у с. Крехів Жовківського р-у Львівської обл.

Today, a dominant trend in factory construction is to account for the eco-economic aspects of their further operations. It requires sustainable technological solutions taking into account structural specificities or for production technology used. At the same time, the buildings shall be architecturally attractive and distinct. In the paper, the author considered architectural, technological, structural, ecological, and economic factors for the construction of wood-processing and furniture-making facilities. The author analyzed the actual Project Design to build the type of facility in Krekhiv village, Zhovkva district, Lviv region (western Ukraine) as commissioned by a well-known French company (the author has been engaged in the design). The study focused on a wood-processing Woodman company designed for the mid-tech production of edge-glued panels and furniture. According to the design documentation by types of products planned, the Project Design provided for the following production units: unit for wood-sawing and drying; unit for mechanical processing of wood, production of edge-glued panels and furniture; unit for mechanical repairs; and an administrative and services unit. The anticipated annual production capacity is: for edge-glued panels – 600 m³ a year, furniture production – up to 4,000 pc a year.
Experience in design and construction of the production of environmental furniture on the example of the new factory of the company “Woodman” in the village of Krekhov, Lvov region
Keywords: завод; проєктування; ВУДМАН; Крехів; Компанія КРЕАТИВ; plant; design; WOODMAN; Krekhiv; CREATIVE Company; 725.4